The common FTO variant rs9939609 is not associated with BMI in a longitudinal study on a cohort of Swedish men born 1920-1924 - Lannfelt Lars; Axelsson Tomas; Risérus Ulf; Jacobsson Josefin A; Schiöth Helgi B; Fredriksson Robert (BMC, 2009)
Abstract Background Common FTO (fat mass and obesity associated) gene variants have recently been strongly associated with body mass index and obesity in several large studies. Here we set out to examine the association of the FTO variant rs9939609 with BMI in a 32 year follow up study of men born 1920-1924. Moreover, we analyzed the effect of physical activity on the different genotypes. Methods The FTO rs9936609 was genotyped using an Illumina golden gate assay. BMI was calculated using standard methods and body fat was estimated by measuring skinfold thickness using a Harpenden caliper. Physical activity was assessed using a four question medical questionnaire. Results FTO rs9939609 was genotyped in 1153 elderly Swedish men taking part of a population-based cohort study, the ULSAM cohort. The risk of obesity and differences in BMI according to genotype at the ages of 50, 60, 70, 77 and 82 were investigated. We found no increased risk of obesity and no association with BMI at any age with the FTO rs9939609 variant. We found however interaction between physical activity at the age of 50 years and genotype on BMI levels (p = 0.039) and there was a clear trend towards larger BMI differences between the TT and AA carriers as well as between AT and AA carriers in the less physically active subjects. Conclusion Here we found that the well established obesity risk allele for a common variant in FTO does not associate with increased BMI levels in a Swedish population of adult men which reached adulthood before the appearance of today's obesogenic enviroment. There is an interaction between physical activity and the effect of the FTO genotype on BMI levels suggesting that lack of physical activity is a requirement for an association of FTO gene variants to obesity.